The Role of Tec Family Kinases in Inflammatory Processes - Melcher, Martin; Raberger, Julia; Schmidt, Uwe; Unger, Bernd; Ellmeier, Wilfried (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2007)
A variety of different cell lineages of the hematopoietic system are activated during inflammatory processes. These cells not only contribute to the beneficial outcome of an immune response, but can also cause pathology such as autoimmunity as a consequence of extended or uncontrolled reactions. Therefore, an understanding of the basic mechanisms that lead to immune cell activation and the identification of key molecular players will also lead to strategies towards therapeutic manipulation of extended immune reactions. Members of the Tec kinase family (Bmx, Btk, Itk, Rlk and Tec) constitute an important class of non-receptor protein tyrosine kinases that are primarily expressed in the hematopoietic system. They are activated upon a variety of signals and are important participants of major signal transduction pathways in immunological processes. Hence, deficiencies in Tec family kinases cause several immunological defects, both in man and mice. Since Tec family kinases have been shown to function as modulators of immune cell activation, they may provide attractive drug targets for the manipulation of the immune response. In this review, we summarize recent data from studies about the activities of Tec family kinases in inflammatory cells and their role in in vivo models of infection, inflammation and autoimmune diseases.
Keywords: immunity